Satisfaction of Arab school teachers in Israel for distance learning and the difficulties they face during the pandemic Corona - Saleh, Naji Awni (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to examine the extent of teachers ’satisfaction in Arab schools in Israel with distance learning during the period of the spread of Corona disease, and the difficulties they face using the quantitative survey descriptive approach. The tool was represented in a questionnaire distributed to a sample of (30) teachers from Arab schools in Israel from the age group (22-45) years, and the research results found that teachers ’satisfaction with the use of distance learning programs obtained an overall average of (4.05 out of 5), meaning that the degree of satisfaction is (high). The difficulties and challenges facing teachers during distance learning obtained an overall average of (4.16 out of 5), meaning that there are big difficulties are, and finally, the results revealed that there are no statistically significant differences in the degree of teachers’ satisfaction about distance learning during the period of the spread of Corona disease due to variables (gender, educational qualification), Curriculum, grade, and years of experience), and the existence of statistically significant differences in the degree of teachers’ satisfaction attributed to variable of (receiving training related to distance education systems) in favor of teachers who had training on using distance education systems, and the difficulties related to distance education were less than those who did not receive training. Based on these results, the researcher presented a set of recommendations and proposals to train teachers, alleviate difficulties, and enhance their approaches to distance education.